2022
DOI: 10.1002/jcp.30752
|View full text |Cite
|
Sign up to set email alerts
|

HIF‐1α plays an essential role in BMP9‐mediated osteoblast differentiation through the induction of a glycolytic enzyme, PDK1

Abstract: Bone homeostasis is regulated by bone morphogenic proteins (BMPs), among which BMP9 is one of the most osteogenic. Here, we have found that BMP9 rapidly increases the protein expression of hypoxia-inducible factor-1α (HIF-1α) in osteoblasts under normoxic conditions more efficiently than BMP2 or BMP4. A combination of BMP9 and hypoxia further increased HIF-1α protein expression.HIF-1α protein induction by BMP9 is not accompanied by messenger RNA (mRNA) increase and is inhibited by the activation of prolyl hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…Indeed, M1 macrophages secret VEGF and are involved in the initiation of angiogenesis; whereas M2 are responsible for the later stages of angiogenesis, stabilizing the vasculature, and typically secreting PDGF-BB. Consistent with in vitro results, the MSC-encapsulated (2022) showed that incorporating TGF-β1 into Li-based hydrogel promotes both osteogenesis and angiogenesis, in which TGF-β1 guides macrophage polarization toward the M2 phenotype and Li ions enhance osteogenesis. Figure 4 represents how a hydrogel-based scaffold enhances angiogenesis by modulating macrophage phenotype.…”
Section: Hydrogels With Antibacterial and Immunomodulatory Capabilitiessupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, M1 macrophages secret VEGF and are involved in the initiation of angiogenesis; whereas M2 are responsible for the later stages of angiogenesis, stabilizing the vasculature, and typically secreting PDGF-BB. Consistent with in vitro results, the MSC-encapsulated (2022) showed that incorporating TGF-β1 into Li-based hydrogel promotes both osteogenesis and angiogenesis, in which TGF-β1 guides macrophage polarization toward the M2 phenotype and Li ions enhance osteogenesis. Figure 4 represents how a hydrogel-based scaffold enhances angiogenesis by modulating macrophage phenotype.…”
Section: Hydrogels With Antibacterial and Immunomodulatory Capabilitiessupporting
confidence: 82%
“…They reported that the constructed scaffolds supported osteoblast proliferation and osteogenesis and promoted tubule formation. Recently, Amir et al (2022) indicated that HIF-1α plays an indispensable role in BMP-9-mediated preosteoblasts differentiation into osteoblasts and vascularization, whereas HIF-1α knockdown or inhibition significantly suppressed the expression of osteogenic markers and matrix mineralization in a BMP-9-dependent manner. In another study, Guo et al (2020) revealed that the protective activity of salidroside on bone loss is related to its stimulatory effects on angiogenesis-osteogenesis coupling via regulating the HIF-1α/VEGF axis.…”
Section: Importance Of Angiogenesis In Bone Development and Repairmentioning
confidence: 99%
“…As shown in Figure 9D, the KEGG enrichment results showed that the differentially expressed proteins in Hypo‐EVs were highly correlated with Hif‐1, PI3K/AKT, and ECM‐receptor interaction signaling pathways, which are known to be involved in the process of osteogenic differentiation. [ 33b,c,45 ]…”
Section: Resultsmentioning
confidence: 99%
“…Amir M S et al found that in bone homeostasis regulated by bone morphogenetic protein (BMP), BMP9 inhibited PHD-mediated protein degradation under normal conditions and increased osteoblasts protein expression of HIF-1α. This finding means that BMP9 can effectively increase the expression of the HIF-1α protein in combination with hypoxic conditions [12].…”
Section: Hif-1α Regulation On Chondrocyte Survival and Differentiationmentioning
confidence: 81%